Minimasi Biaya Distribusi Makanan Ringan pada UKM Marcuy dengan Metode Stepping Stone, Least Coast, VAM dan MODI - Rina Nurhidayati; Ilham Falani; Aditia Maulana Ahmad Ruchianto; Muhamad Naufal; Tania Nur Azizah; Velyda Noer Praniasty (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: The purpose of this research is to minimization of snack distribution costs at Marcuy SMEs using the Stepping Stone, Least Coast, VAM and MODI Method. Method: This study uses the type of data obtained is secondary data, namely the data obtained directly at UKM Makaroni Cihuy. In data processing, the data is processed using the transportation model, namely the method of Stepping Stone, least cost, vogel approximation and modi. Result: Based on the results of research on UKM Marcuy for ensure product delivery budget process using the Stepping Stone, Least Coast, Vogel Approximattion Method (VAM) and Modified Distribution (MODI) methods. From the calculation using the four methods get the same result, namely the distribution costs incurred are Rp. 31.750,- for the type of product packaging 90 gr and Rp. 67.000,- for the type of product packaging 133 gr. Limitation: This research is limited to the problem of minimizing the cost of distribution of snacks in UKM Marcuy. In addition, this study is also limited by the transportation methods used, including the Stepping stone, Least Cost, VAM, and MODI methods. Contribution: This research is expected to provide an optimal solution to the problem of optimization of distribution costs in UKM Marcuy. Furthermore, this research can be a reference for research related to the implementation of the stepping stone, least cost, VAM, and MODI methods in minimizing distribution costs.